Optimization of canopy management and training systems in Phalsa (Grewia subinaequalis Lin.) under semi-arid zone - Rathore, A.C. (Indian Journal of Agroforestry, 2020)
The experiment was conducted on multipurpose fruit plant in department of horticulture at Chandra Shekhar Azad University of Agricultural and Technology, Kanpur (India) with an objective to optimize the canopy management and training system to achieve sustainable produce. Canopy of plants was headed back in different heights (CM0Â = Control, CM1= 50 cm, CM2 = 100 cm and CM3 = 150 cm) and plants trained with two training systems (Single shoot and Multi shoots system). Phalsa bush topped at 100 cm above ground with single and multi-shoot training system (CM2 T1 and CM2 T2) have increased significantly all the vegetative growth parameters of plant height, average plant spread, pruned dry shoot biomass, pruned dry leaf biomass and fruit yield by 23.4 & 25%, 12.74 & 17.19%, 11.08 & 14.66%, 18.51 & 25.5% and 25.54 & 43.26%, respectively as compare to control. Nutrients added to the field as total nitrogen, phosphorus, potash, calcium and magnesium was recorded as 9.52 & 11.62, 0.73 & 0.90, 3.54 & 4.32, 3.26 & 3.98 and 3.26 & 3.98 kg ha-1 under CM2Â T1 & CM2 T2 treatments, respectively whereas lowest values of total nutrients added back to the soil were observed in control treatments.